The function of estuaries mixing zones in main productivity and nutrient flow of coastal waters - Biswas, Debarghya; Tiwari, Ankita; Murlie, Dr. Sushma (International Journal of Aquatic Research and Environmental Studies, 2025)
Estuaries are centers of primary production and nutrient conversion that enhance food webs and environmental functionality locally and in the surrounding environments. The depth-dependent nutrient conversion and main productivity processes in the water column and seafloor were examined, and the lateral flow of substances and materials through the estuary mouth was determined. As a case study, the impacts of Sea Level Rise (SLR) on production and nutrient changes were anticipated using an estuary characterized by shallower soft-sediment ecosystems. The estuary functioned as a net recipient of dissolved minerals from the coast while simultaneously acting as an indirect export of suspended material and chlorophyll a, reinforcing that estuaries serve as significant nutrient transformation processors. A substantial depth (and light) influence on productivity suggests that escalating environmental obstacles, which diminish light at the seafloor (SLR and heightened turbidity), adversely affect estuarine production. Tidal and weak subtidal benthic ecosystems accounted for most of the estuary’s efficiency, a trend likely applicable to other weak estuaries worldwide. SLR and human interventions that inhibit landward emigration, such as seawalls and armoring, will lead to the degradation of these environments and their essential benefits to neighboring coastal environments.